Optimization of alkali-catalyzed transesterification of rubber oil for biodiesel production & its impact on engine performance. (October 2020) - Vishal, Devesh; Dubey, Shivesh; Goyal, Rahul; Dwivedi, Gaurav; Baredar, Prashant; Chhabra, Mayank
Abstract: Rubber (Hevea brasilienis) is a plantation crop grown in various regions of India. It is a non-edible oil source and has excellent potential for being a biodiesel feedstock. The major problem with crude rubber seed oil is its high free fatty acid (FFA) content (37.46%). The present study has used the Box-Behnken response surface method to minimize the FFA content of the oil. FFA content of 1.31% was obtained with alcohol to oil molar ratio of 6.652:1 and 0.5 wt% of H2SO4 catalyst at a reaction temperature of 63.75 °C in 50 min. The results of engine testing indicated a decrease in fuel consumption by 50.23% for RB10 and 47.74% for RB20 when compared with neat diesel. The thermal efficiency was reduced by 12.16% for RB10 and 14.74% for RB20. The emission analysis revealed that HC emissions were increased by 22.3% for RB10 and by 41.72% for RB20. There was a decrease in NOx emissions by 21.5% for RB10 and by 21.7% for RB20 while the CO2 emissions were reduced by 46.3% for RB10 and 49.54% for RB20 at full loading. The CO emissions were increased by 25% and 37.5% for RB10 and, respectively, when compared with diesel. Highlights: Prospect of rubber seed oil as a potential biodiesel feedstock. Use of Box-Behnken design to minimize the free fatty acid content of the RSO. Acid esterification was done to reduce FFA content from 37.46% to 1.31%. BSFC decreased for RB10 and RB20 and BTE is also decreased for RB10 and RB20 when compared to pure diesel under full loading. Increase in HC and CO emissions and a decrease in NOx and CO2 emissions was noted for RB10 and RB20 .